Radikalisme dan Tantangan Keberagamaan Indonesia di Era Reformasi - Alhilali, Muhorib; Hakim, Luqman Al; Fahmi, Ahmad Shofiyulloh; Prasetio, Galih (Palita: Journal of Social Religion Research, 2025)
Radicalism constitutes a global phenomenon manifesting in numerous countries, with Indonesia serving as a notable example. In the reform era, the advent of a free press gave voice to a plethora of Islamic community groups, including those of a radical disposition. This paper aims to provide a comprehensive review of the form and implementation of radicalism in post-New Order Indonesia, with a focus on its impact on social and religious behavior. The research method employed is descriptive research-based qualitative research, utilizing a social science approach through the lens of social construction theory, in conjunction with religious values. The results indicate that the proliferation of radicalism is attributable to a deficiency in comprehension of the principles of the five principles of the Indonesian constitution (Pancasila) and the concept of religious diversity, leading to assertions of truth and exclusivism in religion (rigidity in thinking and religion). Consequently, the concept of renewal (ijtihad) emerges as a necessity, necessitating the interpretation of religious and social contexts to adjust Indonesian culture, thereby ensuring the preservation of its legacy of moderation in religion. Keywords:  Radicalism, Religious Moderation, Diversity